Changes in soil arthropod functional group in a wheat crop under conventional and no tillage systems in Argentina - Marasas, M.E; Sarandón, S.J; Cicchino, A.C (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2001)
Different functional groups of soil arthropodofauna present in the agro-ecosystem can be severely modified by tillage practices. The abundance of different trophic groups subject to conventional tillage (CT) and no tillage (NT) practices were evaluated compared to a natural field boundary (FB) in a wheat crop. Arthropods were captured using pitfall traps and collected every 20 days during 10 months, and grouped according to their habits in predators, phytophagous and detritivorous. Tillage systems affected the abundance of arthropod fauna and the proportion between different functional groups as regards a FB. Predators constituted the most abundant group of all arthropods captured, and their number was higher under NT than under CT. In CT, an increase in predators was observed only in spring, probably associated with a recolonisation from the adjacent plots of NT. Phytophagous was the least representative group in the three evaluated systems, it was higher under cropped plots (NT and CT) than in the FB, and was not affected by tillage practices. Under NT, the number of predators, remained higher along the crop development. Phytophagous activity in no till plots remains constant. In FB, the number of captured individuals was lower and relatively stable along the whole sampling period than in the cultivated plots. Ploughing action (CT plots) provoked a decrease in the relative importance of predators and an increase in phytophagous as regards those in NT and FB. Total biomass of captured arthropod fauna showed significant differences between treatments, being higher in NT and lower in CT plots. It is concluded that tillage systems affect not only the abundance of arthropod fauna but also the proportion between different functional groups. The consequences of these changes for soil quality are discussed later on.